In vitro evaluation of different liners in microleakage of class II posterior composite restorations - Behnaz Esmaeili; Ainaz Bazazi; Ali Bijani (Tehran University of Medical Sciences, 2012)
Background and Aims: Packable composites with high viscosity might not adapt properly to internal surfaces and cervical areas. The aim of this study was to assess the microleakage of class II posterior composite restorations performed using different methods.Materials and Methods: Ninety proximal cavities were prepared in extracted sound premolar teeth, divided into three groups and filled as follows: 1- packable composite (3M filtek P60), 2-Hybrid composite (Z250) + P60 composite and 3- Resin-modified glass ionomer liner + P60 composite. Afterwards, the samples were immersed in 0.5% Foushin solution and sectioned. Gingival microleakage was then graded. Obtained data were analyzed using paired t-test and analysis of variance. Results: In regard to distal cavities, significant difference was seen between the groups 1 and 3 (P=0.01) as well as groups 2 and 3 (P=0.03). Comparing microleakage of mesial and distal cavities, there was a significant difference in groups 1 (P=0.003) and 2 (P=0.005).Conclusion: Based on the findings of this study, application of Z250 composite had no effect on reduction of microleakage of class II posterior composite restorations. Vitremer liner decreased microleakage in dento-gingival margins.